Comparing the consistency of electrocardiogram interval measurements by resting ECG versus 12‐lead Holter. Issue 5 (4th May 2021) - Mendzelevski, Boaz; Spencer, Christopher S; Freier, Anne; Camilleri, Dorothée; Graff, Claus; Täubel, Jörg
Abstract: In clinical trials, traditionally only a limited number of 12‐lead resting electrocardiograms (ECGs) can be recorded and, thus, long intervals may elapse between assessment timepoints and valuable information may be missed during times when patients' cardiac electrical activity is not being monitored. These limitations have led to the increasing use of Holter recorders which provide continuous data registrations while reducing the burden on patients and freeing up time for clinical trial staff to perform other tasks. However, there is a shortage of data comparing the two approaches. In this study, data from a randomized, double‐blind, four‐period, crossover thorough QT study in 40 healthy subjects were used to compare continuous 12‐lead Holter recordings to standard 12‐lead resting ECGs which were recorded in parallel. Heart rate and QT interval data were estimated by averaging three consecutive heartbeats. Values exceeding the sample average by more than 5% were tagged as outliers and excluded from the analysis. Visual comparisons of the ECG waveforms of the Holter signal showed a good correlation with resting ECGs at matching timepoints. Resting ECG data revealed sex differences that Holter data did not show. Specifically, women were found to have a longer QTcF of 20 ms, while men had a lower heart rate. We found that continuous recordings provided a more accurate reflection of changes in cardiac electrical activity over 24 hr. However, manual adjudication is still required to ensure the quality and accuracy of ECG data, and that only artifacts are removed thereby avoiding loss of true signals.